Rumen bacteria changes in weaned dairy calves fed with additives and their impact on methane emissions - Ariza Nieto, Claudia Janeth; Ortiz Cuadros, Ronnal Esneyder; Parra Forero, Diana Marcela; Sierra Alarcón, Andrea Milena; Mayorga Mogollón, Olga Lucía (Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2022)
In ruminants, there is a potential to manipulate microbiota in early life to have a better chance of producing lasting effects through adult life The rumen bacteria changes and methane emissions were evaluated in dairy calves fed with formulated additives